Dyhydrokaempferol-3-O-Ramnoside from Ethyl Acetate Extract Ki Encok (Plumbago zeynalica L.) Leaves - Nani Suryani; Euis Julaeha; Tati Herlina (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
Plumbago zeynalica L. plant belongs to the Plumbaginaceae family, which is spread as a weed in all tropical and sub-tropical countries, and its abundance is very high in Asia and Africa. P. zeynalica L. plants are ethnopharmacologically used as antitumor, antioxidant, antimicrobial, anticancer, wound healed, and anti-inflammatory. This study aims to isolate secondary metabolites from the fraction of P. zeynalica L. leaf extracts with work stages that included isolation and determination of chemical structures by spectroscopy. Based on the results of the separation and purification of the ethyl acetate fraction obtained isolates in the form of a yellow oil suspected as a flavonoid. The chemical structure of the isolates was identified based on UV-Vis spectroscopy data giving maximum absorption at λmax 339.60 nm and 278.80 nm, which are typical for dihydroflavonol. IR spectroscopy analysis of the isolates provided data information on the presence of aliphatic OH, C-H groups, carbonyl groups (C = O), C = C aromatic groups, and ether strain (C-O-C). NMR data showed that the isolate had the molecular formula of C21H22O10, and its molecular weight confirmed by MS spectrometer was obtained m/z 434. Isolates from this ethyl acetate fraction were suspected as dyhydrokaempferol-3-O-ramnoside or engeletin.